2016
DOI: 10.1103/physreva.93.033835
|View full text |Cite
|
Sign up to set email alerts
|

Classical and quantum-linearized descriptions of degenerate optomechanical parametric oscillators

Abstract: Recent advances in the development of modern quantum technologies have opened the possibility of studying the interplay between spontaneous parametric down-conversion and optomechanics, two of the most fundamental nonlinear optical processes. Apart from practical reasons, such scenario is very interesting from a fundamental point of view, because it allows exploring the optomechanical interaction in the presence of a strongly quantum-correlated field, the spontaneously down-converted mode. In this work we anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 106 publications
(246 reference statements)
0
6
0
Order By: Relevance
“…10a for design layout A. We find that the famous S-shape curve, found in many other fields of science [21], [22], [23], [24], is not altered significantly in the presence of nonlinear damping. Fig.…”
Section: B Influence Of Nonlinear Damping On System Responsementioning
confidence: 70%
“…10a for design layout A. We find that the famous S-shape curve, found in many other fields of science [21], [22], [23], [24], is not altered significantly in the presence of nonlinear damping. Fig.…”
Section: B Influence Of Nonlinear Damping On System Responsementioning
confidence: 70%
“…In view of rapid advances of experimental technologies, our scheme holds the promise to be realizable in a wide range of physical systems [72][73][74][75][76], such as whispering-gallery-mode (WGM) micro-resonators [4,13,77] and superconducting electromechanical systems [74,[78][79][80][81][82][83]. For the optical WGM system, the parametric amplification can be introduced to the high-Q optical mode by cavity enhanced second-order or third-order optical nonlinearities [73,84].…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, the effects of an optical parametric amplifier (OPA) inside the cavity on the optomechanical coupling [9,42], the normal mode splitting [43], the cooling of the mechanical mirror [44] and the realization of strong mechanical squeezing [45] have been discussed, which showed that increasing gain of the OPA enhances the coupling between the movable mirror and the cavity field. Furthermore, the effects of OPA on multipartite entanglement [46], force sensing for a free particle [47], and cooling in nonlinear optomechanical systems [48] have been also discussed.…”
Section: Introductionmentioning
confidence: 99%